Pengaruh Peluang Pertumbuhan dan Ketidakpastian Lingkungan Terhadap Tindakan Manajemen Laba - Aang Kunaifi; Nugroho Priyo Negoro (Faculty of Economic and Business, 2016)
Effect of Growth Opportunities and Environmental Uncertainties To Profit ManagementThe purpose of this study is to investigate the determinant of firm’s earning management by food and beverage industry in Indonesian Stock Exchange (IDX) during 2010-2015. The impact growth opportunity and environmental uncertainty may induce greater manager’s use discretionary accruals as earning management. Furthermore, this study also examines the effect auditor quality on the relationship between growth opportunity and earning management. Using purposive sampling, the sample of this study consist 8 companies are listed on IDX (48 firms-year). The result indicated that firm’s situation under growth opportunity and environmental uncertainty had an impact on the earning management. However, auditor quality proven has an impact on the relationship between growth opportunity and eaning management.DOI: 10.15408/ess.v6i2.3572